Crohn’s Disease: A Surgeon’s Perspective - Parray, Fazl Q. (Medknow Publications, 2011)
Crohn’s disease (CD) is known for wide anatomic distribution, different presentations, life-threatening complications, and multiple modalities of management. Its multiple implications are still unaddressed. Since all the patients do not show a good response to medical modalities of treatment, a significant percentage of these patients are referred to the surgeon for the palliation of complications or for the ultimate curative treatment. Since most surgeons come across such patients only rarely, it is sometimes difficult for them to choose the appropriate procedure at the time of need. Moreover, the various surgical modalities available for the different presentations and complications of the disease have not been adequately discussed. The aim of this review is to offer insight and a detailed account of the management of CD from a surgical perspective. This review offers an overview of the various surgical options available, their utility in context, and an approach to various scenarios of complicated CD.